PENGARUH PUPUK MIKRO MAJEMUK DAN ASAM HUMAT TERHADAP KETERSEDIAAN P DAN HASIL PADI GOGO DI LAHAN PESISIR - RR. Yudhi Harini Bertham; Elvira Elistria Ningrum; R. Teguh Adiprasetyo (BPFP Universitas Bengkulu, 2022)
[THE EFFECT OF MICRO-COMPOUND FERTILIZER AND HUMIC ACID ON AVAILABILITY OF P AND UPLAND RICE YIELD IN COASTAL LAND] Indonesia’s coastal areas are potential for the agriculture. However, coastal areas have poor physical, chemical and biological soil properties that unfavorable to the growth and yield of plants. Upland rice is a food crop that can be developed on coastal land using humic acid technology and micro-compound fertilizers. This study aims to determinate the effect of micro-compound fertilizers and humic acid on phosphor availability and upland rice yields on coastal land. This research was conducted from August to December 2021 in Beringin Raya Sub-District Muara Bangka Hulu, Bengkulu City. Soil and plant analysis was carried out in the Soil Science Laboratory, Faculty of Agriculture, Bengkulu University. This research was organized in Randomized Completely Block Design (RCBD) with 2 factors. The first factor is micro-compound fertilizer which consists of 3 levels, namely 0, 70 and 140 g/ha and the second factor is humic acid which consists of 2 levels, namely 0 and 8 L/ha. Each treatment combination was reploicated 4 times. The results showed that there was no interaction between humic acid and micronutrient fertilizer on the observed variables. The application of humic acid at 8 L/ha increased phosphor available by 27.55%, the root colonization by 20.65%, the population of microorganisms by 14.77%, the number of productive tillers of 15.72% and the weight of the pithy grain per plant by 31.50% as compared to control. Also, the application of micronutrient fertilizer at 140 g/ha increased the weight of 1000 seeds, the number of productive tillers, the pithy grains by 7.22, 18.53, and 27.77% respectively as compared control. It is recommended that the upland rice variety can cultivate in coastal land with the application of 140 g/ha micronutrient fertilizer combined with 8 L/ha of humic acid.